MP-8 Lack of Antibody Formation Against Inactivated Avian Influenza Virus in Ducks and Chickens After Intranasally Immunization - Okti Nadia Poetri; Retno Damayanti Soejoedodo; Ni Luh Putu Ika Mayasari; Ekowati Handharyani; Novera Nirmalasanti (Hemera Zoa, 2018)
Vaccination is one of control strategies implemented in endemic countries such as Egypt and Indonesia [1,2]. Most commercial AI vaccines available in Indonesia are adjuvanted inactivated AI vaccines applied through intramuscular routes. Vaccine application by subcutaneous or intramuscular injection can cause pain and stress in poultry, the route of vaccine through the nasal drip (intranasal) is a more convenient and painless.                However, respiratory applied inactivated influenza is poorly immunogenic. Therefore prior to developing inactivated intranasal vaccine, it is necessary to study  antibody response to inactivated AI virus which exposed through intranasal route. The aim of our research was to determined antibody response of ducks and chickens against avian influenza virus (AIV) subtype H5N1 after intranasally immunization.